2014
DOI: 10.1016/s0972-6292(16)30774-4
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of Left Atrial Pressure is a Good Predictor of Freedom From Atrial Fibrillation

Abstract: BackgroundIt is suggested that an elevated left atrial pressure (LAP) promotes ectopic beats emanating in the pulmonary veins (PVs) and that LAP might be a marker for structural remodeling. This study aimed to identify if the quantification of LAP correlates with structural changes of the LA and may therefore be associated with outcomes following pulmonary vein isolation (PVI).MethodsWe analysed data from 120 patients, referred to PVI due to drug-refractory atrial fibrillation (AF) (age 63±8; 57% men). The max… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…Although the greatest clinical utility concerns LASr in the case of echocardiography and LAPmean in the case of hemodynamic measurements, the importance of other LAS and LAP values is also increased. A study revealed that both LAPmax and LAPmean were significantly higher in patients with AF recurrence after catheter ablation [30]. In that study, in multivariate analysis, an LAPmax >18 mm Hg was significantly associated with an elevated risk for AF recurrence (hazard ratio [HR], 3.8).…”
Section: Discussionmentioning
confidence: 94%
“…Although the greatest clinical utility concerns LASr in the case of echocardiography and LAPmean in the case of hemodynamic measurements, the importance of other LAS and LAP values is also increased. A study revealed that both LAPmax and LAPmean were significantly higher in patients with AF recurrence after catheter ablation [30]. In that study, in multivariate analysis, an LAPmax >18 mm Hg was significantly associated with an elevated risk for AF recurrence (hazard ratio [HR], 3.8).…”
Section: Discussionmentioning
confidence: 94%
“…The elevation of LAP also shortens the effective refractory period of cardiomyocytes and increases the chances of developing AF [25]. LAP was related to left atrial structural remodeling [26]. Some studies found that plasma CTRP3 levels were associated with hypertension, coronary heart disease, and heart failure, and CTRP3 inhibited myocardial fibrosis in myocardial infarction rats.…”
Section: Discussionmentioning
confidence: 99%
“…Transseptal LAP was measured as described previously [13, 14]. For the ablation procedure, access was achieved from the femoral veins.…”
Section: Methodsmentioning
confidence: 99%